2007
DOI: 10.1128/mcb.01590-06
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinase 1 Is a Novel Negative Regulator of E-Cadherin-Based Cell-Cell Contacts

Abstract: Cadherins are the most crucial membrane proteins for the formation of tight and compact cell-cell contacts. Cadherin-based cell-cell adhesions are dynamically established and/or disrupted during various physiological and pathological processes. However, the molecular mechanisms that regulate cell-cell contacts are not fully understood. In this paper, we report a novel functional role of casein kinase 1 (CK1) in the regulation of cell-cell contacts. Firstly, we observed that IC261, a specific inhibitor of CK1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 40 publications
0
79
0
3
Order By: Relevance
“…Two kinases were markedly better recovered in the BL-ZO-1 samples: MARK2 (Fig. 4, third row, left), which is involved in microtubule dynamics, Wnt signaling, and cell polarization (33) and casein kinase 1 ␣ (KC1A; third row middle), which partially colocalizes with E-cadherin in MDCK cells (34). Phosphorylation of E-cadherin by KC1A inhibits its localization to cell contacts, negatively regulating cell adhesion (34).…”
Section: Specific Proteins Are Differentially Tagged In Cells Expressmentioning
confidence: 99%
See 1 more Smart Citation
“…Two kinases were markedly better recovered in the BL-ZO-1 samples: MARK2 (Fig. 4, third row, left), which is involved in microtubule dynamics, Wnt signaling, and cell polarization (33) and casein kinase 1 ␣ (KC1A; third row middle), which partially colocalizes with E-cadherin in MDCK cells (34). Phosphorylation of E-cadherin by KC1A inhibits its localization to cell contacts, negatively regulating cell adhesion (34).…”
Section: Specific Proteins Are Differentially Tagged In Cells Expressmentioning
confidence: 99%
“…4, third row, left), which is involved in microtubule dynamics, Wnt signaling, and cell polarization (33) and casein kinase 1 ␣ (KC1A; third row middle), which partially colocalizes with E-cadherin in MDCK cells (34). Phosphorylation of E-cadherin by KC1A inhibits its localization to cell contacts, negatively regulating cell adhesion (34). In addition, KC1A can phosphorylate occludin in vitro, but the functional significance of this is unknown (35).…”
Section: Specific Proteins Are Differentially Tagged In Cells Expressmentioning
confidence: 99%
“…Ncadherin [304] and E-cadherin [305] were shown to be able to directly associate with Lrp5/6. Binding of Wnt morphogens to the Frizzled-LRP5/6 induces a CK1 -dependent phosphorylation of both LRP5/6 and E-cadherin [306] inducing a dissociation of LRP5/6 from E-cadherin [230]. Furthermore, Wnt binding to Frizzled-LRP5/6 induces the phosphorylation of CK1 dependent phosphorylation of p120 (at Ser268 and Ser269) leading to the dissociation of p120 from the E-cadherin complex [230].…”
Section: Connections Between the Wnt-frizzled-lrp5/6 Signalosome And mentioning
confidence: 99%
“…However, there are conflicting data as to whether CKI activity actually is negative for the ␤-catenin/E-cadherin interaction (11,12). We have previously shown that Wnt-5a activates CKI␣ in human breast epithelial cells (16).…”
Section: Wnt-5a Affects ␤-Catenin/e-cadherinmentioning
confidence: 99%
“…GSK-3␤ 2 and CK2 have been implicated as potential kinases. In contrast, phosphorylation of serine 846 by CKI and tyrosine phosphorylation of both E-cadherin and ␤-catenin has been suggested to decrease the association (10,11), although conflicting data are present (12). Still, there is little evidence concerning ␤-catenin phosphorylation and E-cadherin association.…”
mentioning
confidence: 99%